Should I stay, or should I go? – How fund dynamics influence venture capital exit decisions. Issue 1 (9th October 2015) - Bock, Carolin; Schmidt, Maximilian
Abstract: We investigate the determinants of venture capital (VC) exit behavior after the lockup expiry in initial public offerings (IPOs) by considering insights from prospect theory and behavioral finance for the first time. Hereby, the paper concentrates on the under‐researched relationship between fund managers and the limited partners investing in these funds. The results from a proprietary dataset of 292 U.S. VC‐backed IPOs from 1991 to 2008 imply that VC firm characteristics and fund dynamics have a significant influence on the exit extent after the lockup expiry and may not always be in line with limited partners' interests, hinting at the relevance of behavior grounded in prospect theory. In particular, first‐time funds keep their shares longer after an IPO, whereas funds satisfied with current fund performance cash out soon after the end of the lockup period.